(untitled) (Papeles, 2026)
Introduction: The evolution of education toward the era of Artificial Intelligence demands teaching and learning processes that directly impact student knowledge and behavior. Therefore, there is a need to innovate in methodologies that involve all students, considering their different abilities and skills. Methodology: The present study aimed to evaluate the effectiveness of the new teaching strategy called REAPSES method (Learning Style Corners for Primary, Secondary and Higher Education, both university and non-university) in the development of key competencies. This intervention was designed exclusively for educators and professionals within the educational sector. A quasi-experimental design with repeated measures, pretest and posttest, was used with a single group, involving professionals and students in the education field. Data were collected using the Honey-Alonso Learning Styles Questionnaire (CHAEA), the Creativity Questionnaire (CREA), and a training evaluation survey. Results and discussion: The results indicate that the REAPSES Method significantly develops creativity, regardless of the participants’ predominant learning style. Furthermore, a notable increase in participants’ knowledge of the method and high satisfaction with the training were observed. Conclusions: This evidence suggests that methodology transcends disciplinary barriers, fostering essential transversal skills for the current educational context and adapting effectively to the diversity of learning styles.